2022
DOI: 10.1093/genetics/iyac011
|View full text |Cite
|
Sign up to set email alerts
|

GABAA α subunit control of hyperactive behavior in developing zebrafish

Abstract: GABAA receptors mediate rapid responses to the neurotransmitter GABA and are robust regulators of the brain and spinal cord neural networks that control locomotor behaviors, such as walking and swimming. In developing zebrafish, gross pharmacological blockade of these receptors causes hyperactive swimming, which is also a feature of many zebrafish epilepsy models. Although GABAA receptors are important to control locomotor behavior, the large number of subunits and homeostatic compensatory mechanisms have chal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 85 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…The cischlordane-induced behavior is also distinct from both the picrotoxin-treated zebrafish here and recent work in which the expression of individual and different combinations of GABA A subunits were mutated in zebrafish, again confirming that cischlordane disrupts different or additional mechanisms than GABA A receptors. 38 While the zebrafish still develop during our test period, intact NMJs are formed before the treatment began, thus leading us to hypothesize that these observations are not driven by developmental defects. The lack of observed muscle fiber organization abnormalities also supports this.…”
Section: Treatment Of Zebrafish Embryos With Cis-chlordane Results In...mentioning
confidence: 92%
See 1 more Smart Citation
“…The cischlordane-induced behavior is also distinct from both the picrotoxin-treated zebrafish here and recent work in which the expression of individual and different combinations of GABA A subunits were mutated in zebrafish, again confirming that cischlordane disrupts different or additional mechanisms than GABA A receptors. 38 While the zebrafish still develop during our test period, intact NMJs are formed before the treatment began, thus leading us to hypothesize that these observations are not driven by developmental defects. The lack of observed muscle fiber organization abnormalities also supports this.…”
Section: Treatment Of Zebrafish Embryos With Cis-chlordane Results In...mentioning
confidence: 92%
“…Additionally, cis- chlordane induced a unique larval zebrafish touch-evoked behavioral response culminating in decreased swimming efficiency, further illustrating the degeneration of the motor system. The cis -chlordane-induced behavior is also distinct from both the picrotoxin-treated zebrafish here and recent work in which the expression of individual and different combinations of GABA A subunits were mutated in zebrafish, again confirming that cis- chlordane disrupts different or additional mechanisms than GABA A receptors . While the zebrafish still develop during our test period, intact NMJs are formed before the treatment began, thus leading us to hypothesize that these observations are not driven by developmental defects.…”
Section: Resultsmentioning
confidence: 99%
“…They are involved in the regulation of multiple neural circuits, especially in regulating autonomic and motor behaviours 60 . Recently, it was reported that disrupting the normal development of GABAergic neurons during the early developmental stage of zebrafish leads to hyperactive motor behaviours 61 , 62 . Similarly, a study conducted on mice has demonstrated that dysfunction of ventral tegmental area GABA neurons can cause hyperactivity and manic-like behaviour 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Cleft lip and cleft palate mutants also have been tested [ 92 ]. Edited zebrafish are used to study feeding behavior [ 93 ], social behavior [ 94 , 95 ], hyperactivity [ 96 ], domestication patterns [ 97 ], and circadian rhythms [ 98 ]. These models are used to study the genetic basis of disease development and drug testing.…”
Section: Genome Editing In Salmonidae and Cyprinidae Aquaculture Fish...mentioning
confidence: 99%